Técnicas expositivas y logro de competencias en el área de ciencias sociales en estudiantes del segundo grado de educación secundaria de la Institución Educativa Teniente Manuel Clavero Muga, Iquitos 2021 - Flores Diaz, Veronica Valeria (2022)
The objective of this research was: To determine the degree of relationship between the expository technique and the achievement of competences in the CC. SS Area. of students of the 2nd of Secondary, I.E "Manuel Clavero Muga of the city of Iquitos during the year 2021. The research was descriptive correlational. The general design of the research was the non-experimental one and the specific design was the correlational transectional one. The population under study consisted of 131 students and the sample consisted of 56 students. The selection of the sample was intentional non-random extracted from the sample design for populations less than 1,500 based on the Statistical Equation for Population Proportions. The most important results are: X2c = 12.79 > X2t = 5.191, gl = 2, p < 0.05, concluding that the Expository Technique is related to the Achievement of Competencies in the Area of Social Sciences.